High-adhesion organic silicon optical adhesive composition as well as preparation method and application thereof

By using a high-bonded silicone optical glue composition in optical bonding glue, combined with specific formulas and additives, the problem of poor performance of existing optical bonding glue in high temperature and long-term stability environments is solved, and the effects of high bonding strength, excellent durability and good thermal stability are achieved.

CN119614146APending Publication Date: 2025-03-14HANGZHOU XINYU JINGYUAN NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411873159.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing optical bonding glues have poor performance in high temperatures or environments requiring long-term stability, and the acrylic optical bonding glue has problems such as large shrinkage, easy yellowing and difficulty in completely curing in black border areas.

Method used

A high bond silicone optical glue composition is used, including components A and components B, and a colloid with high bond strength, excellent durability and good thermal stability is formed by a specific formula ratio and the addition of active tackifiers, self-synthesis adhesive promoters and special structural polydimethylsiloxanes.

Benefits of technology

High bonding strength, excellent durability and good thermal stability are achieved, the volume shrinkage is less than 0.1%, the light transmittance is greater than 99%, and the energy storage modulus is always maintained above 0.02Mpa in an environment of 0-150°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614146A_ABST
    Figure CN119614146A_ABST
Patent Text Reader

Abstract

The invention discloses a high-adhesion organic silicon optical adhesive composition and a preparation method and application thereof, the high-adhesion organic silicon optical adhesive composition comprises a component A and a component B. The component A comprises the following components in parts by mass: 1.0-5.0 parts of organic silicon resin, 35.0-55.0 parts of vinyl-terminated polydimethylsiloxane, 2.0-8.0 parts of polydimethylsiloxane with a special structure, 10.0-15.0 parts of a cross-linking agent, 2.0-5.0 parts of an active tackifier, 0.01-0.05 part of an inhibitor and 10.0-30.0 parts of a chain extender; the component B is prepared from the following components in parts by weight: 0.3 to 2.0 parts of active catalyst, 1.0 to 5.0 parts of self-synthesized adhesion promoter and 25.0 to 45.0 parts of vinyl terminated polydimethylsiloxane; wherein the component A and the component B are mixed according to the mass ratio of 10: (1-2). The organic silicon optical cement composition provided by the technical scheme has the characteristics of high bonding strength, excellent durability, stable size, optical transparency and better thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optical adhesive tapes, and in particular to a high-adhesion organic silicon optical adhesive composition and a preparation method and application thereof. Background Art

[0002] With the rapid development and popularization of the touch screen electronic product market, consumers' performance requirements for electronic products are constantly increasing, especially in terms of display effects, dust and water resistance, and mechanical strength. In order to keep the touch screen clear under strong external light and solve the light loss problem of the air layer between the touch screen and the display panel, touch screen manufacturers have introduced a full bonding process. Among them, silicone optical bonding glue fills the air layer inside the display screen and improves the visual effect. Optical bonding silicone OCA (Optical Clear Adhesive: high-transparent bonding sheet) is a key material that can be used as an adhesive between optical components in the touch screen, encapsulate the optical devices inside the touch screen, prevent dust, moisture, gas, etc. from affecting the optical devices, ensure the close fit and optical performance between the components, and improve its stability and reliability.

[0003] Adhesive technology is the basis of optical bonding technology. OCA film with high bonding strength can provide strong adhesion, ensure the firmness of the bonding interface, and withstand external stress and load, thereby increasing the reliability and durability of bonding. Silicone optical bonding adhesive is mainly made of silicone material, and its chemical structure is Si-O-Si bond. This non-polar structure gives it high transparency, excellent heat resistance and chemical stability, but also limits the bonding performance after curing. Conventional optical bonding adhesives include acrylic resins, unsaturated polyesters, polyurethanes, epoxy resins, etc. Among them, due to the good adhesion of the polar chemical bond structure to the substrate, acrylic resins and epoxy resin optical bonding adhesives are gradually used in various fields such as packaging, construction, automobiles, and electronics. However, with the increase in the size of touch screens and the promotion of industrial applications, the shortcomings of acrylic optical bonding adhesives are gradually emerging. During use, the size shrinkage rate of acrylic optical bonding adhesives is greater than 2%, and problems such as easy yellowing, excessive size shrinkage, and difficulty in complete curing in the black edge area have occurred.

[0004] In certain applications in the optical field, such as high temperatures or environments that require long-term stability, its performance may not be as good as that of silicone optical bonding adhesives. At this stage, optical bonding adhesives that have excellent stability and high bonding strength, and can quickly adhere and remain adhered after a certain pressure, are urgently needed to be developed. Summary of the invention

[0005] In order to solve the above-mentioned technical problems, the purpose of the present invention is to provide a high-adhesion silicone optical adhesive composition and its preparation method and application, wherein the silicone optical adhesive composition has the characteristics of high bonding strength, excellent durability, stable size, optical transparency and good thermal stability.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:

[0007] A high-adhesion organic silicon optical adhesive composition comprises component A and component B, wherein, by weight,

[0008] Component A includes: 1.0-5.0 parts of silicone resin, 35.0-55.0 parts of vinyl-terminated polydimethylsiloxane, 2.0-8.0 parts of special structure polydimethylsiloxane, 10.0-15.0 parts of crosslinking agent, 2.0-5.0 parts of active tackifier, 0.01-0.05 parts of inhibitor and 10.0-30.0 parts of chain extender;

[0009] Component B includes: 0.3-2.0 parts of active catalyst, 1.0-5.0 parts of self-synthesized adhesion promoter and 25.0-45.0 parts of vinyl-terminated polydimethylsiloxane;

[0010] Component A and component B are mixed in a mass ratio of 10:1-2.

[0011] Preferably, the active tackifier is represented by the following structural formula (1):

[0012]

[0013] Preferably, the self-synthesized adhesion promoter is represented by the following structural formula (2):

[0014]

[0015] Preferably, the special structure polydimethylsiloxane is acryloxypropyl modified polysiloxane, such as structural formula (3), wherein 3≤m≤6, 1≤n≤4;

[0016]

[0017] Wherein, R1 is shown in structural formula (4):

[0018]

[0019] R2 is vinyl, methoxy or ethoxy.

[0020] Preferably, the silicone resin is a combination of one or more of a solvent-free silanol-modified silicone resin and a vinyl MDQ resin, wherein the silanol group content in the silanol-modified silicone resin is 0.01-1wt% and the viscosity is 3000-6000mPa.s; and the vinyl content in the vinyl MDQ resin is 0.02-3wt% and the viscosity is 4000-9000mPa.s.

[0021] Preferably, the cross-linking agent is hydrogen-terminated polydimethylsiloxane, which includes one or a combination of side hydrogen-containing silicone oil and hydrogen-containing MDT resin, and the hydrogen content is 0.04-1.5wt%; the chain extender is hydrogen-terminated polydimethylsiloxane, which includes one or a combination of end hydrogen-containing silicone oil and end side hydrogen-containing silicone oil, and the hydrogen content is 0.01-0.8wt%.

[0022] Preferably, the catalyst is a Custer catalyst or an isopropanol solution of chloroplatinic acid, and the platinum content is 2000-5000 ppm.

[0023] Preferably, the inhibitor is any one or a combination of tetramethyldivinyldisiloxane, tetramethyltetravinylcyclotetrasiloxane, 2-methyl-3-butyn-2-ol, ethynylcyclohexanol, diallyl maleate and diisooctyl maleate.

[0024] A method for preparing the high-adhesion organic silicone optical adhesive composition as described above comprises the following steps:

[0025] (1) Preparation of component A: 1.0-5.0 parts of silicone resin, 35.0-55.0 parts of vinyl-terminated polydimethylsiloxane, 2.0-8.0 parts of special structure polydimethylsiloxane, 10.0-15.0 parts of crosslinking agent, 2.0-5.0 parts of active tackifier, 0.01-0.05 parts of inhibitor and 10.0-30.0 parts of chain extender are weighed respectively by weight, and added to a vacuum mixer in sequence, stirred evenly, and then filled and sealed with nitrogen protection;

[0026] (2) Preparation of component B: 0.3-2.0 parts by weight of active catalyst, 1.0-5.0 parts by weight of self-synthesized adhesion promoter and 25.0-45.0 parts by weight of vinyl-terminated polydimethylsiloxane are added into a vacuum mixer and stirred. The obtained product is filtered and dispensed into designated containers in the dark.

[0027] (3) Mixing and curing: Mix component A and component B in a weight ratio of 10:1-2, place in a high-speed vacuum degassing machine for degassing, and finally fill and store at room temperature;

[0028] The curing conditions are: curing temperature 70°C, curing time: 15 minutes.

[0029] An application of the high-adhesion organic silicone optical adhesive composition as described above in the full bonding of high-performance PC display panels, large-screen vehicle display modules or mobile phone OLED / LCD display modules.

[0030] The present invention has the following beneficial effects due to the adoption of the above technical solution:

[0031] The acetyl group (-COCH3) contained in the active tackifier and the nitrogen atom in the pyridine ring (-C5H4N) are both polar and can form hydrogen bonds, electrostatic attraction and other interactions with other polar molecules or active groups on the surface (such as hydroxyl, carboxyl, etc.). The active tackifier contains amino (-NH) and acetyl carbonyl (-C=O), which can form hydrogen bonds with hydroxyl or amine groups in other materials. These hydrogen bonds play a bonding role between the material interfaces and increase the bonding strength. The nitrogen atom on the pyridine ring can also act as a hydrogen bond acceptor and interact with the surface material containing hydrogen bond donors to further enhance the bonding force. This polarity and the formation of hydrogen bonds can help the active tackifier to produce strong physical or chemical adsorption with the material surface, thereby enhancing the bonding force.

[0032] In the self-synthesized adhesion promoter, the addition of epoxy groups can react with the silicon-hydrogen bonds in the organosilicon material to form new chemical bonds, thereby enhancing the bonding strength between the organosilicon material and other substrates, and is not easily affected by environmental factors. The addition of an appropriate amount of phenyl groups in the self-synthesized adhesion promoter can stabilize the overall colloidal structure and has strong resistance to the effects of the atmosphere, moisture, chemical media, bacteria, etc., so it can be used in many harsh environments. Moreover, the active tackifier can participate in the cross-linking reaction with the self-synthesized adhesion promoter through its amino group to form a chemical bond connection and form a synergistic effect. The existence of this chemical bond further improves the strength and stability of the bond, especially under high temperature or harsh environment. The aromatic pyridine ring structure provides a planar electron cloud distribution, which helps to interact with other aromatic or planar structure molecules (such as organosilicon polymers, etc.) through van der Waals forces. These weak intermolecular forces can accumulate during the bonding process, further improving the 24-hour bonding strength.

[0033] Special structure polydimethylsiloxane is acryloxypropyl modified polysiloxane. By introducing acrylic acid groups into the molecular structure, it has strong weather resistance and aging resistance. The acrylic acid groups have stable polarity and good thermal stability, which can reduce the degradation rate of silicone materials in ultraviolet light, high temperature and oxygen environments, and extend the service life of the materials. The introduction of polar acrylic acid groups increases the polarity of silicone materials, making the surface of silicone materials more easily interact with polar groups (such as hydroxyl, carboxyl, amino, etc.), enhancing the wettability and distribution of adhesives on the surface of materials. After the polar acrylic acid groups react chemically with other materials, they help to enhance the bonding strength and stability with other materials, and can form stronger bonding properties. On the other hand, the acryloxy group contains active double bonds (C=C), which can participate in cross-linking reactions under free radical polymerization or addition reaction conditions. When the acryloxy group is combined with the silicone material, it can form a cross-linked network through free radical polymerization or form covalent bonds with other molecules (such as amino compounds, etc.) through ring-opening polymerization of double bonds. This chemical cross-linking greatly enhances the strength and durability of the adhesive layer, because the covalent bond provides a strong chemical bond that can resist external mechanical stress or environmental changes. This cross-linked structure increases the internal strength of the material and enhances the adhesion. The concentration and distribution of acryloyloxy groups can adjust the density of the cured network. Therefore, by controlling the amount of acryloyloxy groups introduced, the hardness, elasticity and bonding strength of the adhesive material can be customized to meet different bonding requirements.

[0034] After the organic silicon optical adhesive provided by the present invention is cured, the appearance is colorless and transparent, the transmittance is greater than 99%, the volume shrinkage is less than 0.1%, the haze is not greater than 0.2%, the peel strength on the polarizer interface is 7.2-7.8N / 25mm, the peel strength on the PET / glass interface is 18.9-20.2N / 25mm, the bonding strength is high, the dimensional shrinkage is small, the storage modulus is always maintained above 0.02Mpa in an environment of 0-150°C, the adhesive has good thermal stability, and can be filled and stored at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is the storage modulus of the optical bonding adhesive provided in Example 1 and Comparative Examples 1 to 3 of the present invention at 20-150°C. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] In the present invention, the synthesis steps of the adhesion promoter are as follows:

[0038] (1) 37 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 50 parts of toluene solvent were added to a reaction bottle and heated to 60° C., and then 0.3 parts of a 1 wt % dilute hydrochloric acid solution was added, and the mixture was stirred at 350 rpm for 1 hour.

[0039] (2) The temperature was raised to 75° C., and then 18 parts of heptamethylphenylcyclotetrasiloxane were added dropwise under a constant pressure dropping funnel for 15 minutes. After reacting for 2 hours, 5 parts of octamethylcyclotetrasiloxane and 20 parts of toluene were added dropwise. After reacting for 4 hours under nitrogen protection, the temperature was lowered to room temperature and the stirring reaction was stopped. After dehydration with anhydrous sodium sulfate and filtration, the liquids were separated and purified by rotary evaporation to obtain an adhesion promoter.

[0040] The preparation steps of special structure polydimethylsiloxane are as follows:

[0041] (1) 32 parts of octamethylcyclotetrasiloxane (D4), 19 parts of tetramethyltetravinylcyclotetrasiloxane (D4-VI) and 50 parts of toluene as solvent were added to a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel. The internal and external temperatures of the water bath were maintained at 55° C. Under constant temperature stirring in the water bath, 0.4 g of a 10% sodium bicarbonate solution was added, and then the temperature was raised to 75° C. and the reaction was carried out at a constant temperature for 3 hours to obtain a polysiloxane main chain reactant. The reactant was subjected to rotary evaporation to remove the solvent, and then condensed and refluxed for standby use.

[0042] (2) Weigh 5 parts of 1,2-propylene glycol diacetate, 5 parts of methyl methacrylate and 50 parts of toluene respectively, add them into a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a constant pressure dropping funnel, and stir them evenly; add 0.5 parts of ammonium persulfate at a temperature of 75° C., stir evenly and then slowly drip the polysiloxane main chain reactant in step (1), continue stirring and react for 6 hours after dripping, evaporate the reactant to remove the solvent, condense and reflux to obtain polydimethylsiloxane with a special structure.

[0043] Embodiment 1:

[0044] A high-adhesion organic silicon optical adhesive composition, wherein, by weight,

[0045] Component A includes: 3.0 parts of silanol modified silicone resin, 45.0 parts of vinyl terminated polydimethylsiloxane with a viscosity of 10000 mPa.s and a vinyl content of 0.15 wt%, 6.0 parts of special structure polydimethylsiloxane, 15.0 parts of side hydrogenated silicone oil with a viscosity of 200 mPa.s and a hydrogen content of 0.22 wt%, 5.0 parts of active tackifier, 0.03 parts of methyl butynol, and 26.0 parts of end hydrogenated silicone oil with a viscosity of 500 mPa.s and a hydrogen content of 0.12 wt%;

[0046] Component B includes: 0.3 parts of commercially available Custer catalyst, 3.0 parts of self-synthesized adhesion promoter, and 45.0 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 300 mPa.s and a vinyl content of 0.63 wt %; wherein component A and component B are mixed at a mass ratio of 10:1.

[0047] The preparation method of the high-adhesion silicone optical bonding adhesive composition is as follows:

[0048] (1) Preparation of component A: 3.0 parts of silanol-modified silicone resin, 45.0 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 10000 mPa.s and a vinyl content of 0.15 wt%, 6.0 parts of special structure polydimethylsiloxane, 15.0 parts of side hydrogenated silicone oil with a viscosity of 200 mPa.s and a hydrogen content of 0.22 wt%, 5.0 parts of active tackifier, 0.03 parts of methyl butynol, and 26.0 parts of end hydrogenated silicone oil with a viscosity of 500 mPa.s and a hydrogen content of 0.12 wt% were weighed respectively by weight, and added to a vacuum mixer in sequence, stirred evenly, and then filled and sealed with nitrogen protection;

[0049] (2) Preparation of component B: 0.3 parts of a commercially available Custer catalyst, 3.0 parts of a self-synthesized adhesion promoter, and 45.0 parts of a vinyl-terminated polydimethylsiloxane having a viscosity of 300 mPa.s and a vinyl content of 0.63 wt% were weighed respectively by weight, and the above raw materials were added to a vacuum mixer and stirred. The obtained product was filtered and dispensed into a designated container in the dark;

[0050] (3) Mixing and curing: Mix component A and component B in a weight ratio of 10:1, place in a high-speed vacuum degassing machine for degassing, and finally fill and store. Coat or pot when using.

[0051] The filled glue in Example 1 was introduced into the coating production line, wherein the release force of the heavy release type was 0.05 N / 20 mm, the release force of the light release type was 0.07 N / 20 mm, and the curing conditions were: curing at a temperature of 70° C. for 15 min.

[0052] Embodiment 2:

[0053] A high-adhesion organic silicon optical adhesive composition, wherein, by weight,

[0054] Component A includes: 4.0 parts of silanol modified silicone resin, 55.0 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 60000 mPa.s and a vinyl content of 0.05 wt%, 8.0 parts of special structure polydimethylsiloxane, 13.0 parts of side hydrogen-containing silicone oil with a viscosity of 200 mPa.s and a hydrogen content of 0.22 wt%, 5.0 parts of active tackifier, 0.03 parts of diallyl maleate, and 20.0 parts of end hydrogen-containing silicone oil with a viscosity of 80 mPa.s and a hydrogen content of 0.15 wt%;

[0055] Component B includes: 0.3 parts of a commercially available Custer catalyst, 3.0 parts of a self-synthesized adhesion promoter, and 45.0 parts of a vinyl-terminated polydimethylsiloxane having a viscosity of 300 mPa.s and a vinyl content of 0.63 wt%;

[0056] Component A and component B are mixed in a mass ratio of 10:1.

[0057] The preparation method of the high-adhesion silicone optical bonding adhesive composition is as follows:

[0058] (1) Preparation of component A: 4.0 parts of silanol-modified silicone resin, 55.0 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 60,000 mPa.s and a vinyl content of 0.05 wt%, 8.0 parts of special structure polydimethylsiloxane, 13.0 parts of side hydrogenated silicone oil with a viscosity of 200 mPa.s and a hydrogen content of 0.22 wt%, 5.0 parts of active tackifier, 0.03 parts of diallyl maleate, and 20.0 parts of end hydrogenated silicone oil with a viscosity of 80 mPa.s and a hydrogen content of 0.15 wt% were weighed respectively by weight, and added into a vacuum mixer in sequence and stirred evenly, and then filled and sealed with nitrogen protection;

[0059] (2) Preparation of component B: 0.3 parts of a commercially available Custer catalyst, 3.0 parts of a self-synthesized adhesion promoter, and 45.0 parts of a vinyl-terminated polydimethylsiloxane having a viscosity of 300 mPa.s and a vinyl content of 0.63 wt% were weighed respectively by weight, and the above raw materials were added to a vacuum mixer and stirred. The obtained product was filtered and dispensed into a designated container in the dark;

[0060] (3) Mixing and curing: Mix component A and component B in a weight ratio of 10:1, place in a high-speed vacuum degassing machine for degassing, and finally fill and store. Coat or pot when using.

[0061] The filled glue in Example 2 was introduced into the coating production line, wherein the release force of the heavy release type was 0.05 N / 20 mm, the release force of the light release type was 0.07 N / 20 mm, and the curing conditions were: curing at 70° C. for 15 min.

[0062] Example 3

[0063] A high-adhesion organic silicon optical adhesive composition, wherein, by weight,

[0064] Component A comprises: 3.0 parts of silanol modified silicone resin, 35.0 parts of vinyl terminated polydimethylsiloxane with a viscosity of 5000 mPa.s and a vinyl content of 0.45 wt%, 7.0 parts of special structure polydimethylsiloxane, 15.0 parts of side hydrogenated silicone oil with a viscosity of 60 mPa.s and a hydrogen content of 0.62 wt%, 5.0 parts of active tackifier, 0.03 parts of methyl butynol, and 21.0 parts of end hydrogenated silicone oil with a viscosity of 500 mPa.s and a hydrogen content of 0.12 wt%;

[0065] Component B includes: 0.3 parts of a commercially available Custer catalyst, 3.0 parts of a self-synthesized adhesion promoter, and 45.0 parts of a vinyl-terminated polydimethylsiloxane having a viscosity of 300 mPa.s and a vinyl content of 0.63 wt%;

[0066] Component A and component B are mixed in a mass ratio of 10:1.

[0067] The preparation method of the high-adhesion silicone optical bonding adhesive composition is as follows:

[0068] (1) Preparation of component A: 3.0 parts of silanol-modified silicone resin, 35.0 parts of vinyl-terminated polydimethylsiloxane with a viscosity of 5000 mPa.s and a vinyl content of 0.45 wt%, 7.0 parts of special structure polydimethylsiloxane, 15.0 parts of side hydrogenated silicone oil with a viscosity of 60 mPa.s and a hydrogen content of 0.62 wt%, 5.0 parts of active tackifier, 0.03 parts of methyl butynol, and 21.0 parts of end hydrogenated silicone oil with a viscosity of 500 mPa.s and a hydrogen content of 0.12 wt%, and add them in a vacuum mixer in sequence and stir evenly, then fill and seal with nitrogen protection;

[0069] (2) Preparation of component B: 0.3 parts of a commercially available Custer catalyst, 3.0 parts of a self-synthesized adhesion promoter, and 45.0 parts of a vinyl-terminated polydimethylsiloxane having a viscosity of 300 mPa.s and a vinyl content of 0.63 wt% were weighed respectively by weight, and the above raw materials were added to a vacuum mixer and stirred. The obtained product was filtered and dispensed into a designated container in the dark;

[0070] (3) Mixing and curing: Mix component A and component B in a weight ratio of 10:1, place in a high-speed vacuum degassing machine for degassing, and finally fill and store. Coat or fill when using;

[0071] The filled glue is introduced into the coating production line, wherein the release force of the heavy release type is 0.05N / 20mm, the release force of the light release type is 0.07N / 20mm, and the curing conditions are: curing at 70°C for 15 minutes.

[0072] Comparative Example 1:

[0073] The only difference between this comparative example and Example 1 is that no self-synthesized adhesion promoter is added.

[0074] Comparative Example 2:

[0075] The only difference between this comparative example and Example 2 is that no special structure polysiloxane is added.

[0076] Comparative Example 3:

[0077] The difference between this comparative example and Example 3 is only that no active tackifier is added.

[0078] Performance Testing:

[0079] 1. The light transmittance and haze are tested according to the method in the national standard GB / T 2410-2008 Determination of light transmittance and haze of transparent plastics;

[0080] 2. Volume shrinkage is tested according to ASTM C1241-14 Standard Test Method for Volume Shrinkage of Latex Sealants During Curing;

[0081] 3. The peel strength is tested according to the national standard GB / T 2792-2014 test method for peel strength of adhesive tape.

[0082] 4. Storage modulus is tested according to ASTM E2254-18 standard test method for storage modulus calibration of dynamic mechanical analyzer;

[0083] The requirements for optical bonding adhesive compositions in the industry are: transmittance ≥ 99.0, volume shrinkage ≤ 0.2, haze ≤ 0.2%, peel strength (polarizer) ≥ 4.20N / 25mm, peel strength (PET / glass) ≥ 15.0N / 25mm.

[0084] The optical bonding adhesive compositions provided in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for performance according to the above method. The test results are shown in Table 1:

[0085] Table 1 Curing performance of the optical bonding adhesive composition provided in Examples 1 to 3 and Comparative Examples 1 to 3

[0086]

[0087] According to the test results in Table 1, the optical bonding adhesive composition prepared by Example 1 has the best comprehensive performance after curing, specifically, the light transmittance is 99.3%, the volume shrinkage is 0.09%, the haze is 0.15%, the peel strength (polarizer) is 7.8N / 20mm, and the peel strength (PET / glass) is 14.1N / 20mm. The volume shrinkage and glass strength are far better than the requirements of the optical bonding adhesive composition in the industry. By comparing the data of Example 1 with those of Comparative Examples 1-3, it can be seen that the self-synthesized adhesion promoter, the special structure polysiloxane and the active tackifier can significantly improve the peel strength of the optical bonding adhesive composition and significantly improve the bonding ability of the optical bonding adhesive composition.

[0088] The storage modulus of the optical bonding adhesive composition in Example 1 at 20-150°C was tested. The storage modulus of the optical bonding adhesive composition in Example 1 was always maintained above 0.02Mpa in an environment of 0-150°C, and it had good thermal stability. The change in storage modulus can intuitively reflect the degree of curing of the polymer. The degree of curing or depth of curing is directly related to the functional groups such as ester bonds, ether bonds, and acryloyloxy groups in the self-synthesized adhesion promoter and the special structure polysiloxane. Active tackifiers and self-synthesized adhesion promoters can form covalent bonds with other molecules (such as amino compounds in active tackifiers, epoxy group polymers in self-synthesized adhesion promoters, etc.) through ring-opening polymerization of double bonds. This chemical cross-linking greatly enhances the strength and durability of the adhesive layer, and can form a cross-linked inter-transmission network between silicone molecules and between silicone and other materials. This network structure enhances the mechanical strength and degree of curing inside the material, and also improves the overall stability of the adhesive layer. Because covalent bonds provide strong chemical bonding forces that can resist external mechanical stress or environmental changes, and form hydrogen bond network structures with resins, silicone oils, etc., they can effectively improve the bonding performance to various substrates. The silicone part also greatly improves the compatibility with colloids and has almost no effect on transparency.

[0089] All features described in the description, the attached claims and the drawings are essential features for the invention both individually and in any combination.

[0090] Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Ordinary technicians in the field can change, modify, replace, modify, delete some features, add features or re-combine features to form a technical solution in the above embodiments without departing from the principles and purpose of the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the innovative principles of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A high-adhesion silicone optical adhesive composition, characterized in that: It comprises component A and component B, wherein, by weight, Component A includes: 1.0-5.0 parts of silicone resin, 35.0-55.0 parts of vinyl-terminated polydimethylsiloxane, 2.0-8.0 parts of special structure polydimethylsiloxane, 10.0-15.0 parts of crosslinking agent, 2.0-5.0 parts of active tackifier, 0.01-0.05 parts of inhibitor and 10.0-30.0 parts of chain extender; Component B includes: 0.3-2.0 parts of active catalyst, 1.0-5.0 parts of self-synthesized adhesion promoter and 25.0-45.0 parts of vinyl-terminated polydimethylsiloxane; Component A and component B are mixed in a mass ratio of 10:1-2.

2. A high-adhesion organic silicone optical adhesive composition according to claim 1, characterized in that: The active tackifier is shown in the following structural formula (1):

3. The high-adhesion organic silicone optical adhesive composition according to claim 1, characterized in that: The self-synthesized adhesion promoter is shown in the following structural formula (2):

4. The high-adhesion organic silicone optical adhesive composition according to claim 1, characterized in that: The special structure polydimethylsiloxane is an acryloxypropyl modified polysiloxane, such as structural formula (3), wherein 3≤m≤6, 1≤n≤4; Wherein, R1 is shown in structural formula (4): R2 is vinyl, methoxy or ethoxy.

5. The high-adhesion organic silicone optical adhesive composition according to claim 1, characterized in that: The organic silicone resin is a combination of one or more of a solvent-free silanol-modified organic silicone resin and a vinyl MDQ resin, wherein the silanol group content of the silanol-modified organic silicone resin is 0.01-1wt% and the viscosity is 3000-6000mPa.s; and the vinyl content of the vinyl MDQ resin is 0.02-3wt% and the viscosity is 4000-9000mPa.s.

6. The high-adhesion organic silicone optical adhesive composition according to claim 1, characterized in that: The crosslinking agent is hydrogen-terminated polydimethylsiloxane, which includes one or a combination of side hydrogen-containing silicone oil and hydrogen-containing MDT resin, and the hydrogen content is 0.04-1.5wt%; the chain extender is hydrogen-terminated polydimethylsiloxane, which includes one or a combination of end hydrogen-containing silicone oil and end side hydrogen-containing silicone oil, and the hydrogen content is 0.01-0.8wt%.

7. The high-adhesion organic silicone optical adhesive composition according to claim 1, characterized in that: The catalyst is a Custer catalyst or an isopropanol solution of chloroplatinic acid, and the platinum content is 2000-5000ppm.

8. The high-adhesion organic silicone optical adhesive composition according to claim 1, characterized in that: The inhibitor is any one or a combination of tetramethyldivinyldisiloxane, tetramethyltetravinylcyclotetrasiloxane, 2-methyl-3-butyn-2-ol, ethynylcyclohexanol, diallyl maleate and diisooctyl maleate.

9. A method for preparing a high-adhesion organic silicone optical adhesive composition as claimed in any one of claims 1 to 8, characterized in that: The steps include: (1) Preparation of component A: 1.0-5.0 parts of silicone resin, 35.0-55.0 parts of vinyl-terminated polydimethylsiloxane, 2.0-8.0 parts of special structure polydimethylsiloxane, 10.0-15.0 parts of crosslinking agent, 2.0-5.0 parts of active tackifier, 0.01-0.05 parts of inhibitor and 10.0-30.0 parts of chain extender are weighed respectively by weight, and added to a vacuum mixer in sequence, stirred evenly, and then filled and sealed with nitrogen protection; (2) Preparation of component B: 0.3-2.0 parts by weight of active catalyst, 1.0-5.0 parts by weight of self-synthesized adhesion promoter and 25.0-45.0 parts by weight of vinyl-terminated polydimethylsiloxane are added into a vacuum mixer and stirred. The obtained product is filtered and dispensed into designated containers in the dark. (3) Mixing and curing: Mix component A and component B in a weight ratio of 10:1-2, place in a high-speed vacuum degassing machine for degassing, and finally fill and store at room temperature; The curing conditions are: curing temperature 70°C, curing time: 15 minutes.

10. An application of the high-adhesion organosilicon optical adhesive composition as claimed in any one of claims 1 to 8 in the full bonding of high-performance PC display panels, large-screen vehicle display modules or mobile phone OLED / LCD display modules.

Citation Information

Cited By

  • Special high-temperature-resistant and high-light-transmittance silica gel lens for vehicle lamp and preparation method thereof

    CN120737613A